Investigation of Financial Literacy Attitudes of University Students in Terms of Some Demographic Characteristics: The Example of Mus Alparslan University Social Sciences Vocational School - Dündar, Ahmet; Şekeroğlu, Bengü (My University, 2024)
Financial literacy enables effective planning of the financial future by accurately analyzing the current financial situation. In our country, which has a young population, high financial literacy levels of university students will contribute to the country's economy. This study aims to determine the financial literacy knowledge levels of university students. In addition, it focuses on examining financial attitudes and behaviors, which are two important components of financial literacy, in terms of demographic characteristics. In addition, the results of the research aim to determine financial literacy training for college students and to develop strategies on the subject. The study consists of 280 university students from different departments of Muş Alparslan University Social Sciences Vocational School in the 2021-2022 academic year. According to the results of the study, it is seen that 41.8 %of university students have a low level of financial literacy, 43.6 % have a medium level of financial literacy, and 14.6 % have a high level of financial literacy. In addition, it is seen that there is a significant difference in the sub-dimensions of expenditure, attitude, perception, and the total score of financial literacy attitude and behavior according to financial literacy knowledge level. According to financial literacy attitude and behavior levels; A significant difference was found in the sub-dimension of expenditure according to gender and education, expenditure according to the time spent at the university, and perception according to attitude and working status. A correlation test was conducted to find the relationship between the age financial literacy attitude, and behavior levels of students. The results revealed a low-level negative significant relationship between the age of the students and the sub-dimensions of expenditure and perception.
Keywords: Financial Literacy; Financial Behavior; Financial Attitude